The Mediating Role of Satisfaction in the Impact of Complaint Handling and Service Quality on Loyalty of Independent BPJS Health Participants - Oktarina, Desi; Septiano, Renil; Sari, Laynita; Marwan, Marwan; Lusiana, Lusiana (Dinasti Review, 2025)
This study aims to examine the influence of complaint handling and service quality on the loyalty of independent BPJS Health participants, with participant satisfaction acting as a mediating variable. A quantitative approach was employed using the SEM-PLS method, involving 251 respondents in Sijunjung Regency. The findings reveal that both complaint handling and service quality positively affect participant satisfaction. However, complaint handling has a negative impact on loyalty, indicating that negative experiences continue to influence participants even after their complaints are addressed. Meanwhile, satisfaction significantly mediates the relationship between service quality and participant loyalty.